Confucianism in the eyes of a Confucian liberal : Hsu Fu-kuan's critical examination of the Confucian political tradition - Liu, Honghe, 1952- (Asian thought and culture, 2001)
"This book provides access to the work of a contemporary Chinese thinker, Hsu Fu-kuan, whose works may not be accessible to English readers. As a scholar of depth, acumen, and originality, Hsu endeavors to explore the core value of Confucian humanism and to dissociate it from the baneful or outdated bequest. He attributes the political failures of the culture not to the Confucian tradition, but to a legalistically influenced model of "One-Man Despotism," and argues that democracy is the only way forward for China. In analyzing Hsu's thought, this book clearly summarizes the very complex historical trends in Chinese political philosophy and practice spanning centuries. It also explores the possibility of the creative interaction between, and integration of, Confucian humanism and democratic liberalism, as a viable way to solve the moral, spiritual, and ideological problems of China."--BOOK JACKET.